Determination method for carbon and sulfur content in ultra-low carbon austenitic stainless steel

By cutting, grinding and cleaning the sample, combined with strict reagent impurity removal and infrared analysis technology, the problem of accuracy in determining the carbon sulfur content in ultra-low carbon austenitic stainless steel is solved, and high-precision and low-error detection results are achieved.

CN119901701APending Publication Date: 2025-04-29GUANGDONG GUANGQING METAL TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510037252.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

It is difficult to accurately determine the extremely low content of carbon and sulfur in ultra-low carbon austenitic stainless steel, and is affected by factors such as minor contamination, sample preparation and treatment methods, and fluctuations in instrument blank values.

Method used

Granular samples were prepared by cutting and grinding, and cleaned with anhydrous ethanol; oxygen, porcelain crucibles and tungsten flux were strictly removed; infrared carbon sulfur analyzer combined with multi-point fitting correction technology was used for detection.

Benefits of technology

It significantly reduces the risk of sample contamination, improves the uniformity of components and detection accuracy, effectively reduces system errors, and ensures the accuracy of detection results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119901701A_ABST
    Figure CN119901701A_ABST
Patent Text Reader

Abstract

The invention discloses a method for measuring the carbon and sulfur content in ultra-low carbon austenitic stainless steel, and relates to the technical field of stainless steel carbon and sulfur content measurement, and the method comprises the following steps: preparing a sample into a clean granular sample through cutting, polishing and absolute ethyl alcohol cleaning, carrying out special treatment on used oxygen, a porcelain crucible and a tungsten particle fluxing agent, and determining the carbon and sulfur content in the ultra-low carbon austenitic stainless steel. And reducing the blank value of the system and controlling the blank value in a stable range, calibrating the analytical instrument in a multipoint fitting calibration manner, and finally determining the carbon and sulfur content in the sample to be tested by using the calibrated instrument. According to the invention, the to-be-detected sample is prepared into the clean granular sample, and the system blank is reduced to an extremely small stable value, so that the risk that the sample is polluted can be obviously reduced, the system error is avoided, and the accuracy of the detection result is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of measuring the carbon and sulfur content of stainless steel, and particularly relates to a method for measuring the carbon and sulfur content in ultra-low carbon austenitic stainless steel. Background Art

[0002] Ultra-low carbon austenitic stainless steel is a special austenitic stainless steel with a carbon content of less than 0.03%. Its representative steel grades include 304L (022Cr19Ni10), 316L (022Cr17Ni12Mo2), and 317L (022Cr19Ni13Mo3). In stainless steel, as the carbon content decreases, the sensitivity to intergranular corrosion and the risk of carbide precipitation also decrease. Therefore, ultra-low carbon austenitic stainless steel not only has excellent welding performance and corrosion resistance, but also maintains a perfect balance between high strength and corrosion resistance. Thanks to these excellent properties, ultra-low carbon austenitic stainless steel is widely used in food processing equipment, chemical industry, medical equipment, petrochemical industry and other fields, becoming an indispensable material in industrial production and daily life.

[0003] In the production process of ultra-low carbon austenitic stainless steel, the content of carbon and sulfur is a crucial quality indicator and must be strictly controlled. Carbon is a key element to stabilize the austenite structure and expand its area, but when welding or heating to 450℃~850℃, carbon may react with chromium in the steel to form Cr23C6 type carbides, resulting in a local reduction in chromium content, thereby reducing the steel's resistance to intergranular corrosion. Sulfur, as a harmful element, reduces the thermoplasticity of stainless steel, affects hot working properties, and reduces corrosion resistance. Its content is usually controlled below 0.0035%. Therefore, when smelting and processing ultra-low carbon austenitic stainless steel, accurate determination of carbon and sulfur content at each processing stage is crucial to ensure steel quality.

[0004] The infrared absorption method after combustion in a high-frequency induction furnace is a commonly used technology for detecting the carbon and sulfur content in stainless steel. It has the advantages of simple operation and high detection efficiency. However, due to the extremely low carbon and sulfur content in ultra-low carbon austenitic stainless steel, factors such as slight pollution in the detection environment, sample preparation and processing methods, and fluctuations in the instrument blank value will affect the accuracy of the test results. This has brought challenges to the production and industrial improvement of ultra-low carbon austenitic stainless steel. Summary of the invention

[0005] The object of the present invention is to provide a method for determining the carbon and sulfur content in ultra-low carbon austenitic stainless steel to solve the problems raised in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solution: a method for determining the carbon and sulfur content in ultra-low carbon austenitic stainless steel, comprising the following steps: Step 1: Prepare the sample to be tested, cut the stainless steel sample into granular samples with a mass between 0.5-1.0g, and finely grind the surface and cut surface of the granular sample; Step 2: Place the polished granular sample in anhydrous ethanol, clean it in an ultrasonic cleaner for 3-5 minutes, transfer it to a flat weighing bottle, dry it in a forced air drying oven at 50-70°C for 0.5-1h, and store it in a desiccator after the anhydrous ethanol evaporates; Step 3: Use high-purity oxygen with a purity of ≥99.99% to test the sample, adjust the oxygen inlet pressure to 0.2-0.4MPa, and make the oxygen flow through a purification tube filled with magnesium perchlorate and carbon dioxide absorbent before entering the high-frequency induction furnace to remove moisture and carbon dioxide from the oxygen; Step 4: Place the porcelain crucible in a muffle furnace at 1000-1300°C and burn it for 0.5-2 hours. After cooling, store it in a desiccator and use tweezers to pick it up when using it. Step 5: Put the tungsten flux into anhydrous ethanol, clean it in an ultrasonic cleaner for 3-5 minutes, dry it in a blast drying oven at 50-70℃ for 0.5-1h, then keep it in a muffle furnace at 300-400℃ for 0.5-1.5h, and finally take it out and put it in a dryer for use; Step 6: Create an analysis method, start the instrument analysis system, add an analysis method, edit the method name, and set general parameters and element parameters; Step 7: Input the content information of the standard sample required for sample testing into the analysis system; Step 8: Preheat the instrument, clean the combustion chamber and gas system of the instrument, then accurately weigh 0.5-1.0g of stainless steel sample and place it in a porcelain crucible, then weigh 1.0-1.5g of tungsten flux and evenly cover the surface of the stainless steel sample, place the porcelain crucible with the sample on an infrared carbon-sulfur analyzer for analysis, and repeat 3-5 times; Step 9: Analyze the blank value of the system. Accurately weigh 1.0-1.5g of the tungsten flux after heat preservation treatment and place it in a porcelain crucible after high temperature calcination. Analyze it in an infrared carbon-sulfur analyzer. Repeat the analysis of 3-5 sets of blank data until the blank data is stable. Save the detected blank data to the method. The blank value effect will be automatically subtracted from the subsequent calibration and test data. Step 10: Instrument calibration: select multiple stainless steel standard samples with different carbon and sulfur content gradients, calibrate the instrument by multi-point fitting calibration method, analyze each standard sample 3-5 times, select 3 groups of analysis results with similar and stable contents for instrument calibration, and save the calibration curve to the method library; Step 11: Detect the sample to be tested. Accurately weigh 0.5-1.0g of ultra-low carbon austenitic stainless steel sample and place it in a porcelain crucible. Weigh 1.0-1.5g of tungsten flux to cover the surface of the sample. Place the porcelain crucible containing the sample on an infrared carbon-sulfur analyzer for analysis to obtain the carbon and sulfur content in the ultra-low carbon austenitic stainless steel.

[0007] Preferably, in step one, the tool used for cutting is a cutting machine, and the equipment capable of finely grinding the sample surface and the cut surface is a grinder and polisher.

[0008] Preferably, in step 2, after removing grease or other contaminants on the surface of the granular sample, tweezers are used to transfer the cleaned sample to a clean flat weighing bottle.

[0009] Preferably, in step three, the carrier gas purification reagent tube is filled with a carbon dioxide absorbent and a water absorbent for purifying oxygen, which can effectively remove corresponding impurities in oxygen.

[0010] Preferably, in step 4, when the porcelain crucible is placed in the muffle furnace for burning, it must be supported on a dedicated porcelain crucible stand.

[0011] Preferably, in step five, the carbon content in the tungsten particle flux is ≤0.0002%, and the sulfur content is ≤0.0001%.

[0012] Preferably, in steps eight to eleven, the infrared carbon-sulfur analyzer is a Lico infrared carbon-sulfur analyzer, model: CS744.

[0013] Preferably, in step nine, when analyzing the blank value, the frequency of collecting blank value data should be reasonably adjusted according to the performance of the instrument and the changing trend of the blank value to ensure that the collected data can accurately reflect the actual situation of the blank value. At the same time, the blank value data is processed and analyzed using a data analysis algorithm to improve the accuracy and reliability of blank value determination.

[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. The samples are processed into granular specimens by cutting and grinding, and the samples are thoroughly cleaned with anhydrous ethanol to prepare clean granular specimens to remove potential impurities and oil stains. Compared with the planing and drilling methods, this method significantly reduces the risk of sample contamination and ensures the uniformity of the composition and higher detection accuracy.

[0015] 2. Before sample testing, the oxygen, porcelain crucibles and tungsten flux used are strictly treated to remove impurities. By treating the reagents in advance, the carbon and sulfur content in the reagents can be greatly reduced and kept stable, effectively reducing the adverse effects on the test results, ensuring that the test blank value is reduced to an extremely low level and remains stable, thereby effectively avoiding systematic errors.

[0016] 3. An infrared carbon-sulfur analyzer is used as the detection equipment, and the multi-point fitting correction technology is used to calibrate the instrument. Compared with single-point calibration, this method can provide a wider detection range and improve the accuracy of the test results, thereby effectively overcoming the difficulties of existing detection technologies in accurately determining the carbon and sulfur content in ultra-low carbon austenitic stainless steel. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of the assay method of the present invention.

[0018] Figure 2 This is a granular sample prepared by the present invention. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The present invention provides Figure 1-2 A method for determining the carbon and sulfur content in ultra-low carbon austenitic stainless steel is shown below: 1. Prepare the sample to be tested (1) In order to ensure the uniformity of the sample composition and enhance its representativeness, this method uses cutting to prepare the sample into granular samples, replacing the traditional method of preparing the sample into chips by turning or drilling. This can effectively avoid the introduction of impurities and contamination, and reduce the analytical errors that may be caused during the sample preparation process.

[0021] First, cut the sample into granular samples with a mass between 0.5 and 1.0 g. A sample mass that is too low may lead to a lack of representativeness in the test results, while a sample mass that is too high may cause the sample to burn too violently and produce splashing, which will not only affect the test results but may also damage the analysis equipment.

[0022] (2) Next, use a grinder and polisher to finely polish the surface and cut surface of the sample. This method can remove the oxide film on the surface of the sample and difficult-to-clean attachments, and avoid the heat effect generated during the cutting process, thereby ensuring the accuracy of the subsequent carbon and sulfur content analysis.

[0023] (3) Place the polished sample in anhydrous ethanol and clean it with an ultrasonic cleaner for 3 to 5 minutes to remove grease or other contaminants on the sample surface. Use tweezers to transfer the cleaned sample to a clean flat weighing bottle and dry it in an oven at 50 to 70°C for 0.5 to 1 hour. After the anhydrous ethanol has completely evaporated, cover the bottle cap and store the sample in a desiccator to keep it dry.

[0024] 2. Reagent treatment to reduce system blank value When determining the carbon and sulfur content in ultra-low carbon austenitic stainless steel, it must be taken into account that the untreated oxygen, porcelain crucibles, flux and instrument system used in the experiment may contain an indefinite amount of carbon and sulfur impurities. Usually, the carbon content of these impurities ranges from 0.001% to 0.010%, and the sulfur content ranges from 0.0001% to 0.0010%. Due to the presence of these impurities, the system blank value may sometimes even be higher than the actual content in the sample. During the sample analysis process, these carbon and sulfur impurities will decompose and release as the sample burns at high temperatures, thus affecting the measurement results. Therefore, when conducting the test, it is necessary to fully consider and eliminate the interference of these potential blank values ​​on the final test results.

[0025] (1) Oxygen treatment When determining the carbon and sulfur content in ultra-low carbon austenitic stainless steel, the potentially combustible alkanes, moisture and impurity carbon in the oxygen used will decompose to produce CO2, CO and H2O during the sample combustion process. These decomposition products will cause the carbon test results to be high. At the same time, the moisture adsorbed in the gas pipeline will absorb CO2 and SO2, resulting in low carbon and sulfur test results. If moisture enters the infrared detection cell, it may also cause the sulfur analysis results to be high.

[0026] Therefore, in order to eliminate the interference of oxygen on the test results, try to use high-purity oxygen with a purity of at least 99.99%, rather than ordinary industrial oxygen with a purity of only 99.5%. Before entering the high-frequency induction furnace, high-purity oxygen should be further purified through the carrier gas purification reagent tube and treated with carbon dioxide and water absorbents to minimize the adverse effects of combustible alkanes, moisture and impurity carbon that may exist in oxygen on the test results.

[0027] (2) Treatment of porcelain crucible The porcelain crucible itself contains an indefinite amount of carbon and sulfur, and may be contaminated and absorb moisture during its production, transportation and storage. As the sample burns, the porcelain crucible will decompose CO2, SO2 and H2O, which will produce blank values ​​and affect the test results.

[0028] Therefore, before use, the porcelain crucible needs to be properly pretreated. The treatment steps include burning the porcelain crucible in a muffle furnace at a temperature range of 1000-1300°C for 0.5-2 hours, and storing it in a desiccator after cooling. In order to avoid introducing contaminants during the treatment process, the porcelain crucible should be carried on a dedicated porcelain crucible stand during burning and picked up with tweezers when in use. This method can remove interfering impurities contained in the porcelain crucible itself to the greatest extent.

[0029] (3) Flux treatment The carbon content of pure iron flux is ≤0.0005%, and the sulfur content is ≤0.0003%. In this method, the stainless steel sample used for detection contains a large amount of iron matrix, so only tungsten flux is needed during the analysis process, and there is no need to add pure iron particles as flux, which can avoid the blank introduced by the use of pure iron flux.

[0030] In tungsten flux, the carbon content is ≤0.0002% and the sulfur content is ≤0.0001%, but its surface may still adsorb carbon and sulfur-containing pollutants. In order to further reduce the blank value caused by tungsten flux, the tungsten flux can be placed in anhydrous ethanol and cleaned in an ultrasonic cleaner for 3 to 5 minutes to remove grease or other pollutants on the surface, and then dried in an oven at a temperature of 500 to 70°C for 0.5 to 1 hour. Then, place it in a muffle furnace at a temperature of 300 to 400°C for 0.5 to 1.5 hours, take it out and place it in a dryer for use.

[0031] 3. Establish analytical methods Before testing, a method for determining the carbon and sulfur content in ultra-low carbon austenitic stainless steel is first established on the instrument analysis system. The method should include the following steps: creating a method name, configuring method parameters, entering the details of the calibration standard, and calibrating the instrument using the standard sample to ensure optimal analytical accuracy.

[0032] (1) Creation method Start the instrument analysis system, add the required analysis method, edit the method name, and set the general parameters and element parameters in turn.

[0033] (2) Add standard sample information The content information of the standard sample is needed when inputting the sample into the analysis system for testing. After the analysis method is established, the instrument needs to be calibrated or drift corrected using the standard sample. After the standard sample is calibrated, the calibration curve information will be saved in the analysis method.

[0034] (3) Instrument calibration There are certain differences in the carbon and sulfur contents in different types of ultra-low carbon austenitic stainless steels. Before sample testing, if only a single standard sample is used to calibrate the instrument, the detection range of the calibration curve may be limited, and samples with a large content span may not be accurately measured. However, using a series of standard samples with a wide range of carbon and sulfur contents from low to high to calibrate the instrument can achieve a wider detection range and improve the accuracy and repeatability of the analytical method. Therefore, selecting multiple standard samples with similar carbon and sulfur contents to those in the ultra-low carbon austenitic stainless steel to be tested for multi-point fitting calibration of the instrument is an effective method to ensure that the calibration curve can fully cover the carbon and sulfur content range of the samples to be tested. For each set of standard samples, 3 to 5 sets of data should be analyzed. Only when the measured data are stable and do not exceed the allowable error can these data be used for instrument calibration.

[0035] 4. Determine the carbon and sulfur content in the sample (1) System cleaning During analysis, the dust and moisture adsorbed by the instrument's combustion chamber and gas pipeline will adsorb the carbon and sulfur released by the sample, affecting the test results, so the combustion chamber and gas pipeline system need to be cleaned before testing.

[0036] (2) Instrument preheating Select the established analysis method and add the sample, blank, standard sample and sample detection columns in sequence.

[0037] Subsequently, the instrument enters the preheating stage. Accurately weigh 0.5-1.0g of stainless steel sample and place it in a porcelain crucible. Next, weigh 1.0-1.5g of tungsten flux and evenly cover the surface of the sample. Place the porcelain crucible containing the sample on the infrared carbon-sulfur analyzer for analysis. Repeat this step 3-5 times to ensure that the instrument is fully preheated. The preheating process helps to eliminate condensed moisture and impurity gases that may exist in the pipeline, thereby stabilizing the temperature inside the instrument. This step is crucial to reducing measurement errors caused by temperature fluctuations, ensuring the stability of the instrument's operating state, and reducing the system blank value.

[0038] (3) Analyze the blank value of the system When conducting carbon and sulfur analysis, blank value analysis is a key step, which helps to eliminate systematic errors and thus improve the accuracy of the analysis results.

[0039] The operation steps are: accurately weigh 1.0-1.5g of tungsten flux after heat preservation treatment and place it in a porcelain crucible after high temperature calcination, and then place it in the infrared carbon sulfur analyzer for analysis. Repeat this step to analyze 3-5 sets of blank data until the blank data is stable. Select the detected blank data and save it to the method. The subsequent calibration and test data of this method will automatically subtract the influence of the blank value. The amount of tungsten flux weighed during blank detection is consistent with the amount weighed during instrument calibration and sample detection.

[0040] (4) Instrument calibration Select multiple stainless steel standard samples with different carbon and sulfur content gradients, and calibrate the instrument by multi-point fitting calibration method. Enter the standard samples for instrument calibration in the standard sample detection column in turn, accurately weigh 0.5-1.0g of stainless steel standard sample, place it in a porcelain crucible, then weigh 1.0-1.5g of tungsten flux to cover the sample surface, place the porcelain crucible containing the sample on the infrared carbon and sulfur instrument for analysis, and analyze each stainless steel standard sample 3-5 times. In the measurement data of each standard sample, select 3 groups of analysis results with similar and stable contents for instrument calibration, and save the calibration curve to the method library.

[0041] (5) Testing samples After completing the instrument calibration, accurately weigh out 0.5-1.0g of ultra-low carbon austenitic stainless steel sample and place it in a porcelain crucible. Then, weigh 1.0-1.5g of tungsten flux to cover the surface of the sample. Next, place the porcelain crucible containing the sample on an infrared carbon-sulfur analyzer for analysis to determine the carbon and sulfur content in the ultra-low carbon austenitic stainless steel.

[0042] Example 1: The carbon and sulfur content in a portion of ultra-low carbon austenitic stainless steel is determined using the technical solution provided in the specific implementation method. The specific detection steps are as follows: Main instruments and reagents: Lico infrared carbon-sulfur analyzer, model: CS744; high-purity oxygen, purity ≥99.99%; nitrogen; anhydrous ethanol; ultrasonic cleaner; blast drying oven; cutting machine; grinder and polisher; porcelain crucible for carbon-sulfur analysis; tungsten flux, carbon content ≤0.0002%, sulfur content ≤0.0001%; ​​magnesium perchlorate; carbon dioxide absorbent; stainless steel standard samples: YSBC2811a-13 (C: 0.021%, S: 0.0009%), YSBC28330-13 (C: 0.013%, S: 0.0021%), YSBC28327-13 (C: 0.018%, S: 0.0057%), YSBC28323-13 (C: 0.039%, S: 0.0160%).

[0043] 1. Prepare the samples to be tested (1) The ultra-low carbon austenitic stainless steel sample (taken from the steelmaking workshop, numbered G20241028F01) was cut into three granular samples with similar specifications and a mass of about 0.7 g.

[0044] (2) Use a grinder to finely polish the surface and cut surface of the specimen to remove the oxide layer on the surface of the specimen and eliminate the heat-affected zone that may be generated during the cutting process.

[0045] (3) Place the polished sample in a beaker containing anhydrous ethanol and clean it with an ultrasonic cleaner for 5 minutes. Then, use tweezers to place the cleaned sample in a clean flat weighing bottle and dry it in a forced air drying oven at 60°C for 0.5 h. After the anhydrous ethanol is completely evaporated, cover the bottle cap and store the sample in a desiccator. The masses of the processed samples are 0.5822 g, 0.5986 g, and 0.6043 g, respectively.

[0046] 2. Process reagents and consumables to reduce system blank value In the infrared carbon and sulfur analysis process, untreated reagents often contain carbon, sulfur and moisture with large fluctuations. These components will decompose and release when the sample is burned and exposed to high temperature environment, thus affecting the analysis results to varying degrees. In order to evaluate this effect, this test randomly selected porcelain crucibles and tungsten granule flux without any treatment, and carried out 6 blank tests when the oxygen purification tube failed. In these tests, the amount of tungsten granule flux was 1.5g. The relevant measurement data are shown in Table 1.

[0047] Table 1 Blank value determination results in untreated reagents The test results in Table 1 show that the untreated reagents contain high and volatile carbon and sulfur contents. Therefore, it is necessary to fully consider the possible blank values ​​in each part to eliminate the influence of the blank values ​​on the test results.

[0048] (1) Oxygen treatment Use high-purity oxygen with a purity of ≥99.99% to test the sample, adjust the oxygen inlet pressure to 0.25MPa, and make the oxygen flow through a purification tube filled with magnesium perchlorate and carbon dioxide absorbent before entering the high-frequency induction furnace to remove moisture and carbon dioxide from the oxygen.

[0049] (2) Treatment of porcelain crucible Place the porcelain crucible on a porcelain crucible stand and place it in a muffle furnace at 1100°C for 2 hours to remove the carbon, sulfur and moisture impurities carried by the porcelain crucible. After the burning is completed, let it cool naturally and store it in a desiccator for later use.

[0050] (3) Treatment of tungsten flux Put the tungsten flux into a beaker filled with anhydrous ethanol and clean it in an ultrasonic cleaner for 5 minutes. Then dry it in a 60℃ forced air drying oven for 0.5 hours. After the anhydrous ethanol is completely volatilized, place it in a muffle furnace at a temperature of 350℃ for 1 hour. After that, let the tungsten flux cool naturally and place it in a dryer for use.

[0051] Six groups of blank data were obtained by randomly selecting treated porcelain crucibles, tungsten granule flux and oxygen. 1.5 g of tungsten granule flux was weighed. The measured data are shown in Table 2.

[0052] Table 2 Blank value determination results in treated reagents The measurement results in Table 2 show that in the infrared carbon and sulfur analysis, the blank values ​​of carbon and sulfur in the treated reagents will be greatly reduced, and the blank value of carbon will be stably maintained below 0.00022%, and the blank value of sulfur will be stably maintained below 0.00007%, which can meet the requirements for determining the carbon and sulfur content in ultra-low carbon austenitic stainless steel.

[0053] 3. Establish analytical methods (1) Creation method Turn on the instrument analysis system, add a detection method, name it "Ultra-low carbon austenitic stainless steel", and set the method parameters: purge time is 15s, delay time is 10s, high-frequency furnace power is 100%, comparator level is 1%, minimum integration time is 40s, and maximum integration time is 60s.

[0054] (2) Add standard sample information The names of the stainless steel standard samples used and their carbon and sulfur content information were input into the analysis system, which were YSBC2811a-13 (C: 0.021%, S: 0.0009%), YSBC28330-13 (C: 0.013%, S: 0.0021%), YSBC28327-13 (C: 0.018%, S: 0.0057%), and YSBC28323-13 (C: 0.039%, S: 0.0160%).

[0055] 4. Determine the carbon and sulfur content in the sample Select the established "ultra-low carbon austenitic stainless steel" analysis method, and use the porcelain crucible and tungsten flux treated in step 2 to carry out instrument preheating, blank value determination, instrument calibration and sample testing in sequence. The amount of tungsten flux weighed during the test must remain consistent.

[0056] (1) System cleaning Before testing, clean the gas pipeline, combustion chamber, burner head and other components, and replace the absorbent in the gas purification tube.

[0057] (2) Instrument preheating Turn on the instrument and wait for the instrument to run stably for 0.5 hours. Accurately weigh 0.5g of the same type of stainless steel sample as a "waste sample" and place it in a porcelain crucible, weigh 1.5g of tungsten flux to cover the surface of the sample, and place the porcelain crucible with the sample on the infrared carbon sulfur analyzer for analysis. Repeat this step to test 3 groups of "waste samples" to stabilize the internal temperature of the instrument.

[0058] (3) Analyze the blank value of the system Add a blank test, accurately weigh 1.5g of tungsten flux and place it in a porcelain crucible, then analyze it in an infrared carbon-sulfur analyzer, record the detection values ​​of carbon and sulfur, and repeat this step to analyze 3 to 5 sets of blank data until the blank data is stable.

[0059] Three groups of stable blank data were selected for averaging, and the average values ​​of the measured blank data of carbon (0.00018%) and sulfur (0.00005%) were saved in the method of “ultra-low carbon austenitic stainless steel”. The subsequent calibration data and sample test data of this method will be obtained by automatically subtracting the blank data from the system measured values.

[0060] (4) Instrument calibration In the standard sample detection column, add the stainless steel standard samples for multi-point fitting calibration in sequence, then accurately weigh 0.5g of the stainless steel standard sample and place it in a porcelain crucible, weigh 1.5g of tungsten flux and cover the sample surface, place the porcelain crucible containing the sample on the infrared carbon-sulfur analyzer for analysis, analyze 3 to 5 groups of data for each stainless steel standard sample, select 3 groups of data with similar and stable contents for instrument calibration, and save the calibration curve to the method.

[0061] (5) Determination of carbon and sulfur content in the sample After the instrument calibration is completed, the ultra-low carbon austenitic stainless steel sample prepared in step 1 is placed in a porcelain crucible, 1.5 g of tungsten flux is weighed and covered on the sample surface, and the porcelain crucible containing the sample is placed on an infrared carbon-sulfur analyzer for analysis to obtain the carbon and sulfur content values ​​in the ultra-low carbon austenitic stainless steel. The test data are shown in Table 3.

[0062] Table 3 Carbon and sulfur determination data in ultra-low carbon austenitic stainless steel Example 2: Verification of the precision of the inventive method In order to verify the precision of the determination results of the method of the present invention, one ultra-low carbon austenitic stainless steel sample was prepared into 6 granular samples with similar specifications according to the method provided in Example 1. The determination results of carbon and sulfur content and the precision calculation data (RSD, %) are shown in Table 4.

[0063] Table 4 Precision verification results of the invented method The verification results showed that among the 6 groups of carbon and sulfur data measured, the relative standard deviation (RSD, %) of carbon was 1.36%, and the relative standard deviation (RSD, %) of sulfur was 5.63%. The method of the present invention has good precision.

[0064] Example 3: Verification of the correctness of the invention method In order to verify the accuracy of the measurement results of the method of the present invention, four bulk ultra-low carbon austenitic stainless steel standard samples used for spectral analysis were prepared and measured according to the method provided in Example 1. The comparison results of the measured carbon and sulfur data with the certified values ​​of the standard samples are shown in Table 5.

[0065] Table 5 Correctness verification results of the invention method The verification results show that the carbon and sulfur content data of the spectral standard sample measured by the method of the present invention are basically consistent with the certification data, and the differences are all within the uncertainty range, with a high degree of accuracy.

[0066] The verification results of Example 2 and Example 3 show that the determination results of the method of the present invention are highly accurate and can meet the requirements for determining the carbon and sulfur content in ultra-low carbon austenitic stainless steel.

[0067] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for determining the carbon and sulfur content in ultra-low carbon austenitic stainless steel, characterized in that: The following steps are involved: Step 1: Prepare the sample to be tested, cut the stainless steel sample into granular samples with a mass between 0.5-1.0g, and finely grind the surface and cut surface of the granular sample; Step 2: Place the polished granular sample in anhydrous ethanol, clean it in an ultrasonic cleaner for 3-5 minutes, transfer it to a flat weighing bottle, dry it in a forced air drying oven at 50-70°C for 0.5-1h, and store it in a desiccator after the anhydrous ethanol evaporates; Step 3: Use high-purity oxygen with a purity of ≥99.99% to test the sample, adjust the oxygen inlet pressure to 0.2-0.4MPa, and make the oxygen flow through a purification tube filled with magnesium perchlorate and carbon dioxide absorbent before entering the high-frequency induction furnace to remove moisture and carbon dioxide from the oxygen; Step 4: Place the porcelain crucible in a muffle furnace at 1000-1300°C and burn it for 0.5-2 hours. After cooling, store it in a desiccator and use tweezers to pick it up when using it. Step 5: Put the tungsten flux into anhydrous ethanol, clean it in an ultrasonic cleaner for 3-5 minutes, dry it in a blast drying oven at 50-70℃ for 0.5-1h, then keep it in a muffle furnace at 300-400℃ for 0.5-1.5h, and finally take it out and put it in a dryer for use; Step 6: Create an analysis method, start the instrument analysis system, add an analysis method, edit the method name, and set general parameters and element parameters; Step 7: Input the content information of the standard sample required for sample testing into the analysis system; Step 8: Preheat the instrument, clean the combustion chamber and gas system of the instrument, then accurately weigh 0.5-1.0g of stainless steel sample and place it in a porcelain crucible, then weigh 1.0-1.5g of tungsten flux and evenly cover the surface of the stainless steel sample, place the porcelain crucible with the sample on an infrared carbon and sulfur analyzer for analysis, and repeat this step 3-5 times; Step 9: Analyze the blank value of the system. Accurately weigh 1.0-1.5g of the tungsten flux after heat preservation treatment and place it in a porcelain crucible after high temperature calcination. Analyze it in an infrared carbon-sulfur analyzer. Repeat the analysis of 3-5 sets of blank data until the blank data is stable. Save the detected blank data to the method. The blank value effect will be automatically subtracted from the subsequent calibration and test data. Step 10: Instrument calibration: select multiple stainless steel standard samples with different carbon and sulfur content gradients, calibrate the instrument by multi-point fitting calibration method, analyze each standard sample 3-5 times, select 3 groups of analysis results with similar and stable contents for instrument calibration, and save the calibration curve to the method library; Step 11. Detect the sample to be tested: accurately weigh 0.5-1.0g of ultra-low carbon austenitic stainless steel sample and place it in a porcelain crucible, weigh 1.0-1.5g of tungsten flux to cover the surface of the sample, place the porcelain crucible containing the sample on an infrared carbon-sulfur analyzer for analysis, and obtain the carbon and sulfur content values ​​in the ultra-low carbon austenitic stainless steel.

2. The method for determining the carbon and sulfur content in ultra-low carbon austenitic stainless steel according to claim 1, characterized in that: In step 1, the tool used for cutting is a cutting machine, and the equipment for fine grinding of the sample surface and the cut surface is a grinder and polisher.

3. The method for determining the carbon and sulfur content in ultra-low carbon austenitic stainless steel according to claim 1, characterized in that: In step 2, after removing grease or contaminants from the surface of the granular sample, use tweezers to transfer the cleaned sample to a clean flat weighing bottle.

4. The method for determining the carbon and sulfur content in ultra-low carbon austenitic stainless steel according to claim 1, characterized in that: In step three, the carrier gas purification reagent tube is filled with a carbon dioxide absorbent and a water absorbent for purifying oxygen to remove impurities in the oxygen.

5. The method for determining the carbon and sulfur content in ultra-low carbon austenitic stainless steel according to claim 1, characterized in that: In step 4, when the porcelain crucible is placed in a muffle furnace for burning, a dedicated porcelain crucible stand must be used to support it.

6. The method for determining the carbon and sulfur content in ultra-low carbon austenitic stainless steel according to claim 1, characterized in that: In step 5, the carbon content of the tungsten particle flux is ≤0.0002%, and the sulfur content is ≤0.0001%.

7. The method for determining the carbon and sulfur content in ultra-low carbon austenitic stainless steel according to claim 1, characterized in that: In steps 8 to 11, the infrared carbon-sulfur analyzer is a Lico infrared carbon-sulfur analyzer, model: CS744.

8. The method for determining the carbon and sulfur content in ultra-low carbon austenitic stainless steel according to claim 1, characterized in that: In step nine, when analyzing blank values, the frequency of collecting blank value data is adjusted according to the performance of the instrument and the changing trend of the blank values.